The plausibility of life : resolving Darwin's dilemma - Kirschner, Marc; Gerhart, John, 1936- (Yale University Press, 2005)
In the 150 years since Darwin, the field of evolutionary biology has left a glaring gap in understanding how animals developed their astounding variety and complexity. The standard answer has been that small genetic mutations accumulate over time to produce wondrous innovations such as eyes and wings. Drawing on cutting-edge research across the spectrum of modern biology, Marc Kirschner and John Gerhart demonstrate how this stock answer is woefully inadequate. Rather they offer an original solution to the longstanding puzzle of how small random genetic change can be converted into complex useful innovations. In a new theory they call 'facilitated variation', Kirschner and Gerhart elevate the individual organism from a passive target of natural selection to a central player in the 3-billion-year history of evolution. In clear, accessible language, the authors invite every reader to contemplate daring new ideas about evolution. By closing the major gap in Darwin's theory Kirschner and Gerhart also provide a timely scientific rebuttal to modern critics of evolution who champion 'intelligent design'.